Amortization expenses' influence on financial position of the company - Mijailović Snežana; Ilić Đorđe; Marić Aleksandar (Trendovi u Poslovanju)
Financial strength is a central issue of any business system and is reflected in payment, investing and financing. Depreciation as a form of self-financing aims to create added value company through increase in total revenues and income of a business entity. Since depreciation results from the positive business of the company, it represents its own stable and permanent source or funding available in the most important part of business economics - the process of reproduction. The revaluation of fixed assets, like a derived function of amortization, serves to objectively and more accurately show the property of the company for stakeholders.